Politics of the Corporation. (7th August 2013) - Veldman, Jeroen
Abstract : The corporate form and its capacity for agency is recognized in political theory, but not adequately understood. As a result, important shifts in the relative position of the state and the corporate form are not addressed. Starting with a historical exploration of the theory of the corporation, I show that the corporate form relies on multiple theoretical backgrounds, which makes it inconsistent. An important part of this inconsistency is the dominance of a post‐1970s theory of the corporate form, which formed the background for New Public Management. This theory supported a reduced status of the state and its regulatory powers and an increase of the relative power of the corporate form. I evaluate some consequences of this inconsistent theory for the contemporary debate with regard to the 'demise of the state'.